Adipose tissue-derived injectable products combined with platelet-rich plasma for the treatment of osteoarthritis: the promising preclinical results are not confirmed by the clinical evidence - Simone Orazi; Angelo Boffa; Manuela Salerno; Lucia Angelelli; Stefano Zaffagnini; Giuseppe Filardo (EFORT Open Reviews)
Purpose: The association of adipose tissue-derived injectable products with platelet-rich plasma (PRP) has been promoted for osteoarthritis (OA) treatment. The aim of this study was to investigate the preclinical and clinical evidence supporting the potential of this combined approach to treat OA. Methods: A systematic review was performed in January 2024 on five databases (PubMed, Embase, Scopus, Cochrane, and Web-of-Science) to identify preclinical in vivo and clinical studies. Safety, OA biomarker changes, and outcomes in terms of clinical and imaging results were analyzed. The quality of studies was assessed with the SYRCLE’s tool for preclinical studies and the Downs and Black checklist for clinical studies. Results: Ten preclinical studies (223 animals) and 14 clinical studies (594 patients) were included. Preclinical results documented improvements at the cartilage histological and immunohistochemical evaluation and at the biomarkers level. Clinical studies confirmed the procedure’s safety, and the case series suggested satisfactory results in different joints in terms of symptoms and function improvement, with positive findings at the biomarker level. However, the randomized controlled trials did not document any clinical benefit, nor any changes in the imaging analysis. A large heterogeneity and overall poor quality were documented in both preclinical and clinical studies. Conclusions: There is an increasing interest in the use of adipose tissue-derived injectable products associated with PRP for the treatment of OA joints, with preclinical studies showing promising results with this combined approach. However, clinical studies did not confirm the benefits offered by PRP augmentation to adipose tissue-derived injectable products in patients affected by OA.